Private Peaceful - Morpurgo, Michael (New York Scholastic Press, 2004)
When Thomas Peaceful's older brother is forced to join the British Army, Thomas decides to sign up as well, although he is only fourteen years old, to prove himself to his country, his family, his childhood love, Molly, and himself
11
Keywords: People with mental disabilities -- Fiction; Poverty -- Fiction; Single-parent families -- Fiction; Soldiers -- Fiction; World War, 1914-1918 -- England -- Fiction; Great Britain -- History -- George V, 1910-1936 -- Fiction